Naprawienie szkody w Kodeksie wykroczeń - Liżyńska, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The increasing popularity of restitutive justice in criminal law — characterised by development of measures which enable compensation of damage caused by a crime to the victim and at the same time place the victim of a prohibited act in a signifi cant position in the proceedings — encourage refl ection on the degree to which compensation is refl ected in the petty offence law. The author analyses the penal measure of damage compensation in petty offences. Her de lege ferenda conclusions may contribute to an enhancement of the role of compensation in petty offence law.
Keywords: naprawienie szkody; odszkodowanie; środek karny